Penyuluhan Keluarga Berencana Bagi Wanita Usia Produktif - Kamalyla Agnina (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
One of the main problems facing developing countries, including Indonesia, is rapid population growth. To overcome this problem, the Indonesian government launched the Family Planning (KB) program. The family planning program provides residents with the opportunity to regulate birth spacing or reduce birth rates by using various hormonal and non-hormonal contraceptives. hoping to slow population growth. Family planning is a procedure that helps individuals or couples avoid unwanted births, obtain the births they really want, and regulate birth spacing. Family planning is a conscious process in which a couple decides the number and spacing of children and when they will be born. The aim is to improve the welfare of mothers and children and create happy and prosperous small families by slowing the birth rate and population growth in Indonesia.